Comparative effect of stocking density and flock size on performance and egg quality of laying hens in conventional and furnished California cages - P ROY; M M KADAM; D B BHAISARE; J J ROKADE; S K BHANJA (Indian Journal of Animal Sciences, 2022)
Two experiments were carried out with an objective to test the comparative performance of laying hens reared in conventional California cages vs furnished California cages with regards to production performance, egg quality parameters and immune status. Experiments were conducted at Poultry Research and Training Centre, Department of Poultry Science, Nagpur Veterinary College during 2019-21. Commercial White Leghorn (BV300) hens (n =72) in each experiment were assigned into two treatments with six replicates in conventional and furnished California cages, and reared for a 20 week period. The furnished cages (FC) are provided with perches, nesting area and scratch pad to meet the natural behaviour of the birds. There were two different treatments viz. 548 cm2/b×6 birds and 645cm2/b×6 birds to see the effect of different stocking density in cages. The performance of the laying hens reared in furnished cages were recorded and compared with findings of birds reared in conventional California cages (CC). The results showed that body weight, weight gain, hen day egg production percentages, feed : egg ratio, egg weight and proportion of broken eggs and dirty eggs were not significantly affected by cage types. However, Haugh unit and albumen height of the eggs from furnished cages hens were significantly higher than those from the conventional California cage hens. While H/L ratio and corticosterone values were significantly lowest in furnished cage system birds. It can be concluded from study that the layer birds can be reared in stress free condition in furnished cage system.